Endoplasmic reticulum targeting and insertion of tail-anchored membrane proteins by the GET pathway - Denic, Vladimir; Dötsch, Volker; Sinning, Irmgard (Cold Spring Harbor perspectives in biology, 2013)
Hundreds of eukaryotic membrane proteins are anchored to membranes by a single transmembrane domain at their carboxyl terminus. Many of these tail-anchored (TA) proteins are posttranslationally targeted to the endoplasmic reticulum (ER) membrane for insertion by the guided-entry of TA protein insertion (GET) pathway. In recent years, most of the components of this conserved pathway have been biochemically and structurally characterized. Get3 is the pathway-targeting factor that uses nucleotide-linked conformational changes to mediate the delivery of TA proteins between the GET pretargeting machinery in the cytosol and the transmembrane pathway components in the ER. Here we focus on the mechanism of the yeast GET pathway and make a speculative analogy between its membrane insertion step and the ATPase-driven cycle of ABC transporters.
Gesehen am 11.12.2020